2022
DOI: 10.1021/jacs.1c13432
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen-Atom Defect Formation in Polyoxovanadate Clusters via Proton-Coupled Electron Transfer

Abstract: The uptake of hydrogen atoms (H-atoms) into reducible metal oxides has implications in catalysis and energy storage. However, outside of computational modeling, it is difficult to obtain insight into the physicochemical factors that govern H-atom uptake at the atomic level. Here, we describe oxygen-atom vacancy formation in a series of hexavanadate assemblies via proton-coupled electron transfer, presenting a novel pathway for the formation of defect sites at the surface of redox-active metal oxides. Kinetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
58
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 53 publications
4
58
0
Order By: Relevance
“…Previous work from our group has shown that the BDFE(O–H) of reduced POV-alkoxide clusters can be approximated by monitoring the extent to which H-atom transfer occurs between various organic reagents and a cluster. 12,13 The observation of quantitative reduction of the POV suggests that the BDFE(O–H) of the cluster is sufficiently larger than that of DHP, establishing an effective minimum value of the BDFE(O–H) avg for the reduced cluster in THF. However, despite the fact that there exists a substantial library of known thermochemical parameters of PCET reagents, the BDFE(N–H) avg for DHP is not reported in THF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work from our group has shown that the BDFE(O–H) of reduced POV-alkoxide clusters can be approximated by monitoring the extent to which H-atom transfer occurs between various organic reagents and a cluster. 12,13 The observation of quantitative reduction of the POV suggests that the BDFE(O–H) of the cluster is sufficiently larger than that of DHP, establishing an effective minimum value of the BDFE(O–H) avg for the reduced cluster in THF. However, despite the fact that there exists a substantial library of known thermochemical parameters of PCET reagents, the BDFE(N–H) avg for DHP is not reported in THF.…”
Section: Resultsmentioning
confidence: 99%
“…9,10 To experimentally model mechanisms of PCET at MO x surfaces, researchers have turned to the investigation of their molecular analogues. [11][12][13][14][15][16] One class of compounds that is particularly well-suited for these studies is polyoxometalates (POMs). POMs are three-dimensional MO x assemblies composed of early transition metal oxyanions linked together by edge-or face-sharing oxide ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their synthetic tunability and homogeneous nature, atomically precise nanoclusters are advantageous for this purpose and can serve as both functional models and as platforms for new catalyst development. , Examples of molecular clusters that feature metal/support architectures exist, such as the catalytically competent Au n ( SR ) m clusters in which the reactive surface gold atoms are chemically distinguished from those of the cluster core . While tuning cluster size and the coordination environment of the active sites has been shown to modulate their catalytic activity, studies that identify the active site and systematically correlate how its identity impacts the metal/support interaction and the emerging catalytic activity are yet to materialize.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 More recently, PCET from molecular donors has been used to incorporate hydrogen atom equivalents into metal oxides, allowing for the activation of typically inert substrates by avoiding high-energy intermediates. 11,12 In a similar vein, silylium-coupled electron transfer presents an intriguing alternative to streamline the mechanism of UQO bond activation. Mashima and coworkers have demonstrated that the silyl transfer reagent, 1,4bis(trimethylsilyl)dihydropyrazine, Pyz(SiMe 3 ) 2 , called ''Mashima's reagent'', can facilitate the reduction of transition metals in high oxidation states.…”
mentioning
confidence: 99%